The Influence of Operations Strategy, Innovation and it Readiness on Smart City Implementation in Serang City and its Impact on Public Organization Performance - Zakiyah Zakiyah; Furtasan Ali Yusuf; Uli Wildan (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Globalization and an increase in population have changed urban demography in various countries in the world, including Banten Province, especially in Serang City as the capital of Banten Province. One of the variables that can drive this performance increase is the implementation of smart cities which are considered as a solution to solving current urban problems. The research was conducted on 15 public apparatus organizations using a purposive sampling technique and using as many as 50 indicators to measure each latent variable. The method of analysis in this study uses descriptive index numbers and SEM PLS as inferential analysis. The results showed that 8 hypotheses were accepted while 2 hypotheses were rejected. The operational strategy has a significant effect on the implementation of smart cities and the performance of public organizations.